Evaluating the Real Estate Transaction Process Identifying common practice across the industry and potential for improvements - Carlberg, Josefin; APELQVIST, JONAS (My University, 2018)
The process of a transaction in real estate is characterized by complex networks of involvement from multiple stakeholders. Furthermore, the originality of each transaction necessitates the need for flexibility and adaptation to the process whilst maintaining a level of standardization in the strive to achieve efficiency. The level of complexity and ever-changing contextual factors have created the need for a process which facilitates this type of environment. This thesis seeks to evaluate current common practice and identify possible improvement potential for the transaction process. This thesis focuses on three main point of views, (1) the internal perspective, (2) the external perspective and (3) the comparison of the process between different companies. The projected result was to identify areas where the process could be improved. The investigation of the subject starts with a theoretical collection of knowledge in the subjects of: real estate transaction processes, project management and procurement process theory. Specific sub theories are further investigated based on their application to the phenomenon, examples are soft skills in project management and stakeholder management to name a few. The empirical collection in this thesis include interviews with internal personnel at Willhem, other real estate companies and advisors involved in the process. Results from the study show that the generic characteristics of the process are very similar both between companies, but also in comparison to theory. The interesting findings are instead in the soft areas and regard the application of the process more than the process itself. Lastly, recommendations derive from the analysis of gathered data pertaining the transaction process. One of the main conclusions involve a change in the handling of the process by treating it more as a project process, another to map and understand the stakeholders involved in the process to assure proper handling and involvement.
Keywords: Produktion; Transport; Grundläggande vetenskaper; Hållbar utveckling; Övrig industriell teknik och ekonomi; Production; Transport; Basic Sciences; Sustainable Development; Other industrial engineering and economics